Living in the Red: Black Steelworkers and the Wealth Gap. (March 2017) - Wagner, Venise
A database built from recently released archival bankruptcy records shows that African-American steelworkers compared with white steelworkers were disproportionately represented as bankruptcy petitioners soon after the 1959 national steel strike began. On its face, it would appear that the strike forced low-level workers in the mills toward a financial precipice, but a deeper exploration finds that black steelworkers in Chicago at this time, despite their security in the union, faced a myriad of financial barriers, which when combined hindered workers' ability to build wealth and lead their families into the middle class. Even though black workers enjoyed the benefits of the union's promise to deliver wage and pension security, as well as better workplace conditions, the union failed to address the most pressing matter for black workers—equity in the workplace. In addition, the union's outward look at civil rights did little to combat social policies that left black steelworkers disenfranchised along with other African-Americans in Chicago. Union policies, in contrast, secured coveted positions for white steelworkers in the mills and fortified their ability to build wealth and higher economic status for their families. The combined impact of financial and social barriers for blacks in the mills—workplace segregation, residential segregation, restricted access to mortgage financing, susceptibility to predatory lending, and usurious credit practices—are explored. Michael Brown et al.'s theory of disaccumulation of economic opportunity helps illustrate the enduring wealth gap between white and black workers, even those African-Americans who held well-paying steel manufacturing jobs.